It Takes Two: The Round-Robin Methodology for Investigative Interviewing Research - Hudson, Charlotte A.; Satchell, Liam P.; Adams-Quackenbush, Nicole (Frontiers in Psychology, 2018)
Investigative interviews are complex, dyadic, social interactions typically studied by evaluating interviewers’ questioning strategies. In field settings, interviewers naturally vary in their interviewing practice. Thus, it is important to conduct research reflective of idiosyncrasies in witnesses, interviewers, and the resulting unique pairings. This study explored sources of variation in an interview by using a ‘round-robin’ design. Each session of the study involved five witnesses observing five separate events. Witnesses were then simultaneously, but independently interviewed by four different interviewers, or completed a self-administered written interview. This sequence was repeated until each witness had seen every event and had been interviewed by each interviewer. Over nine sessions (N = 45) this produced 225 total interviews. Individual interview performance (accuracy and level of detail) as well as experience (subjective ratings) were then analysed in relation to the typical performance of the interviewer, the witness, the event, and the unique paring. We found that witnesses and interviewers could have an effect on statement quality, however the unique interview experience variance had the greatest influence on interview performance. This study presents the round-robin methodology as a useful tool to study realistic variation in interviewer, witness, and dyad behaviour. The preprint of this paper is available at psyarxiv.com/tv5gz/, and materials and data are available at osf.io/ef634/files/.